2023
DOI: 10.1002/adma.202212190
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Biointerface for Cardiac Arrhythmia Diagnosis and Treatment

Abstract: Heart rhythm disorders, known as arrhythmias, cause signi cant morbidity and are one of the leading causes of mortality. Cardiac arrhythmias are primarily treated by implantable devices, such as pacemakers and de brillators, or by ablation therapy guided by electroanatomical mapping.Pharmacological treatments are mostly ineffective. Both implantable and ablation therapies require sophisticated biointerfaces for electrophysiological measurements of electrograms and delivery of therapeutic stimulation or ablatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 93 publications
0
17
0
Order By: Relevance
“…Lin et al reported a sub-micrometer-thick graphene array for cardiac arrhythmia diagnosis, supporting sensing and stimulation of the mammalian heart in vitro and in vivo (Figure 26b). 41 The graphene arrays exhibit the ultralow interface impedance of 40 Ωcm 2 (at 1 kHz) with a charge storage capacity of up to 63.7 mC cm −2 . Besides, the transparency of the graphene array enables simultaneous optical mapping of cardiac action potentials, calcium transients, and optogenetic stimulation.…”
Section: Bio-integrated Soft Electronicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lin et al reported a sub-micrometer-thick graphene array for cardiac arrhythmia diagnosis, supporting sensing and stimulation of the mammalian heart in vitro and in vivo (Figure 26b). 41 The graphene arrays exhibit the ultralow interface impedance of 40 Ωcm 2 (at 1 kHz) with a charge storage capacity of up to 63.7 mC cm −2 . Besides, the transparency of the graphene array enables simultaneous optical mapping of cardiac action potentials, calcium transients, and optogenetic stimulation.…”
Section: Bio-integrated Soft Electronicsmentioning
confidence: 99%
“…(b) Schematic illustration of the graphene array for recordings of cardiac electrophysiology and the treatment of cardiac arrhythmia. Adapted with permission from ref . Copyright 2023 Wiley-VCH.…”
Section: Applications For Flexible Electronicsmentioning
confidence: 99%
See 3 more Smart Citations